THE DEVELOPMENT OF STUDENT WORKSHEET PROBLEM SOLVING ORIENTED TO TRAIN STUDENTS CRITICAL THINKING SKILL ON ACID-BASE MATERIAL IN CLASS XI MIPA MAN LAMONGAN (UNESA Journal of Chemical Education, 2018)
This study is aimed to develop student worksheet problem solving oriented to train student critical thinking skill on acid base material. Worksheet based on the steps of problem solving. According to Facione (in Filsaime, 2008), critical thinking skill that can be trained are: interpretation, inference, and analysis. This study is developed by using Research and Development (R & D) of Borg and Gall’s design. The design consists three steps: introduction, development, and test. This study was limited to development. Student worksheet problem solving oriented is declared feasible. It can be seen from the validity, practicality, and effectivity. Worksheet was declared valid in terms of content validity which reached 82.81% and the construct validity which got 79.33%. Student worksheet was declared practical in terms of student responses get a percentage of 78.33% and supported by students activities. Student worksheet is declared effective in accordance with the critical thinking skill test with each student obtaining the value of ≥2.67. Keywords: student worksheet, problem solving, critical thinking skill.